Potensi Hiperglikemia pada Warga Binaan Penyalahguna NAPZA: Deskripsi Gula Darah Puasa dan Karakteristik Metabolik - Aulia Risqi Fatmariza; Danny Meganingdyah Primartati; Angga Eka Kurniawan; Rahmad Darmawan; Aprilia Kusumaningrum (Jurnal Sintesis: Penelitian Sains, Terapan dan Analisisnya, 2026)
Substance abuse can disrupt glucose metabolism and increase the risk of undetected hyperglycemia, particularly in vulnerable populations such as inmates. This study aimed to describe fasting blood glucose levels and metabolic characteristics among substance-abusing inmates. A descriptive cross-sectional study was conducted involving 80 inmates selected by total sampling. Data included fasting blood glucose, body mass index, and blood pressure. Descriptive statistical analysis was performed, including mean, median, standard deviation, range, and proportion of hyperglycemia. The mean fasting blood glucose level was 121.3 mg/dL (median 117 mg/dL; SD 22.77 mg/dL; range 84–204 mg/dL). Hyperglycemia was observed in 42.5% of respondents. A proportion of subjects were also classified as obese and hypertensive. Substance-abusing inmates demonstrate a considerable burden of hyperglycemia, highlighting the importance of routine metabolic screening in correctional settings. Keywords: fasting blood glucose; hyperglycemia; substance abuse; inmates; metabolic risk